Measurement of 89Y(n, 2n) spectral averaged cross section in LR-0 special core reactor spectrum. (December 2017) - Košťál, Michal; Losa, Evžen; Baroň, Petr; Šolc, Jaroslav; Švadlenková, Marie; Koleška, Michal; Mareček, Martin; Uhlíř, Jan
Abstract: The present paper describes reaction rate measurement of 89 Y(n, 2n) 88 Y in a well-defined reactor spectrum of a special core assembled in the LR-0 reactor and compares this value with results of simulation. The reaction rate is derived from the measurement of activity of 88 Y using gamma-ray spectrometry of irradiated Y2 O3 sample. The resulting cross section value averaged in spectrum is 43.9 ± 1.5 µb, averaged in the 235 U spectrum is 0.172 ± 0.006 mb. This cross-section is important as it is used as high energy neutron monitor and is therefore included in the International Reactor Dosimetry and Fusion File. Calculations of reaction rates were performed with the MCNP6 code using ENDF/B-VII.0, JEFF-3.1, JEFF-3.2, JENDL-3.3, JENDL-4, ROSFOND-2010, CENDL-3.1 and IRDFF nuclear data libraries. The agreement with uranium description by CIELO library is very good, while in ENDF/B-VII.0 description of uranium, underprediction about 10% in average can be observed. Highlights: Determination of 89 Y reaction rate in irradiated Y2 O3 sample. Experimental spectral average cross section of 89 Y(n, 2n) reaction. Calculation of reaction rate 89 Y(n, 2n) reaction. Discrepancies between calculation and experiment.